Maritime Dangers Faced by the Seamen of the North of the Crown of Castile in the Later Middle Ages (SP) (Edad Media. Revista de Historia, 2017)
This study is concerned with the dangers faced by the seamen of northern Castile of the coasts of San Vicente de la Barquera, Santander, Laredo and Castro Urdiales –four port towns known in the late Middle Ages as ‘Cuatro Villas de la Costa de la Mar de Castilla Vieja’ [Four Towns of the Sea Coast of the Old Castile]– with other parts of the Bay of Biscay also falling under its scope. The geographical framework used focuses on the Atlantic, although attention has also been paid to the Western Mediterranean. The essay draws on both published and unpublished documents of varied nature: legislative compilations, literature of the time, court papers (lawsuits), images, etc. Our study concludes that the working conditions of seamen and tradesmen were very hard, and they frequently paid with their lives. Despite such high cost, trading and fishing continued, since they were vital for the maintenance of those towns.
Keywords: Castile; Atlantic ocean; sailing; sea; danger